1993
DOI: 10.1021/bi00211a034
|View full text |Cite
|
Sign up to set email alerts
|

The importance of binding energy in catalysis of hydride transfer by UDP-galactose 4-epimerase: A carbon-13 and nitrogen-15 NMR and kinetic study

Abstract: UDP-galactose 4-epimerase contains NAD+ irreversibly but noncovalently bound to the active site. Uridine nucleotides bind to the substrate site and induce a protein conformational change that increases the chemical reactivity of NAD+ at the coenzyme site. Activation of NAD+ by uridine nucleotides perturbs the 15N and 13C NMR chemical shifts of selectively enriched NAD+ bound to the coenzyme site. The proton-decoupled 15N NMR signal for enzyme-bound [carboxamide-15N]NAD+ does not change upon addition of UDP, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 43 publications
5
59
0
Order By: Relevance
“…Theoretical calculations on the nicotinamide indicated that deformation of the pyridine ring into a boat conformation enhances hydride transfer (2). It has been observed by UV-visible spectroscopy and NMR that the puckering of the pyridine ring changes upon enzyme binding (3). Until now it was unclear how an enzyme could steer the puckering of the ring to facilitate hydride transfer.…”
mentioning
confidence: 99%
“…Theoretical calculations on the nicotinamide indicated that deformation of the pyridine ring into a boat conformation enhances hydride transfer (2). It has been observed by UV-visible spectroscopy and NMR that the puckering of the pyridine ring changes upon enzyme binding (3). Until now it was unclear how an enzyme could steer the puckering of the ring to facilitate hydride transfer.…”
mentioning
confidence: 99%
“…It was reported that each subunit of the dimeric epimerase contained one irreversibly, noncovalently bound NAD ϩ (33), and no additional NAD ϩ was required for the epimerase-catalyzed reaction (32). This is also the case for the fusion enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…UDP-Gal 4-epimerase is one of the key enzymes of the Leloir pathway for galactose metabolism (32). The epimerase from E. coli is a homodimer with an overall molecular mass of 79 kDa (33).…”
Section: Discussionmentioning
confidence: 99%
“…Biological phosphates, being achiral or prochiral at tetrahedral phosphorus, had to be synthesized with P-substituents such as S, 18 O, and/or 17 O stereospecifically placed to study stereochemistry (22). The ping-pong mechanism of GalT implied overall retention of configuration at P␣ of UDP-glucose through stereochemical inversion in two steps.…”
Section: Galactose Metabolism In the Leloir Pathwaymentioning
confidence: 99%
“…Our laboratory developed 31 In stereochemical work on phosphotransferases, Pchiral adenosine 5Ј-O-(3- [3-thioate groups in the products were determined by chemical, mass spectrometric, or 31 P NMR methods. R. Douglas Sammons, Thomas Meade, and Radha Iyengar devised methods for displacing sulfur from P-chiral phosphorothioate esters with 18 O or 17 O from water (25, 26). Our group applied these methods to elucidate the stereochemical course of phosphotransfer ( Table 1).…”
Section: Galactose Metabolism In the Leloir Pathwaymentioning
confidence: 99%